Endogenous and Exogenous Factors Affecting Capital Structure: A Theoretical Review - Darmono, Darmono; Su’un, Muhammad; Jillbert , Julius; Ikawijaya, Natali; Mursyidin, Mursyidin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Capital structure refers to the way a company finances its operations through a mix of equity and debt. The choice of capital structure has important implications for the risk and return of a firm, as well as its ability to raise funds and invest in future growth. In this theoretical review, we will examine the endogenous and exogenous factors that affect a firm's capital structure decisions. In conclusion, a firm's capital structure decisions are influenced by a complex set of endogenous and exogenous factors. By understanding these factors, firms can make informed decisions about their capital structure, balancing the trade-offs between risk, return, and growth potential.